Sistem Penanggulangan Bantuan Korban Bencana Berbasis Lokasi Kebencanaan - Reynoldus Andrias Sahulata (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2026)
A total of 204 natural disasters were recorded in Minahasa Utara Regency in 2023, including floods, landslides, strong winds, and fallen trees. A major constraint in disaster management is the imprecise distribution of aid due to poorly recorded logistics data and reporting that is still conducted solely through call centers 112 and 117. To address this issue, assist the study aims to develop Disaster Location-Base System for Post-Disaster Victim Aid Management that can assist the Minahasa Utara Regional Disaster Management Agency (BPBD) in managing, recording, and distributing aid accurately to the intended recipients. The system development methodology used is Extreme Programming (XP), which includes the planning, design, coding and testing stages, with needs analysis involving the BPBD. The system was designed using the Unified Modeling Language (UML). The results of this research is a Web-based system capable of recording logistics, mapping the location of aid recipients, and displaying distribution reports. This system can help accelerate the distribution process, increase the accuracy of aid delivery, and provide accurate data for evaluation purposes for the Minahasa Utara BPBD.